Developing policy-relevant river fish monitoring in Greece: Insights from a nation-wide survey - A. N. ECONOMOU; S. ZOGARIS; L. VARDAKAS; N. KOUTSIKOS; Y. CHATZINIKOLAOU; D. KOMMATAS; Y. KAPAKOS; S. GIAKOUMI; E. OIKONOMOU; V. TACHOS (Mediterranean Marine Science, 2016)
A wide-ranging river fish survey was executed in the summer of 2009 as part of the preparatory actions for the establishment of a monitoring programme for the EU Water Framework Directive (WFD). This was the first extensive electrofishing campaign for WFD standardized bioassessment in Greece and the experience and insights gained are used here to provide a review of fish-based assessment conditions and requirements in this country. The survey sampled 85 sites on 25 rivers throughout mainland Greece, collecting 70 species of freshwater fish. Quantitative site-based assemblage data is used for taxonomic and ordination analyses revealing a strong biogeographic regionalization in the distribution of the ichthyofauna. The structural and spatial organisation of the fish fauna through the use of species-level and community-level data analyses is explored in three ecoregions where data was deemed sufficient. Transitions in community taxonomic composition among ecoregions were abrupt and concordant with geographical barriers and reflect the influence of historical biogeographic processes. Community-based analysis revealed a substantial degree of variation in quantitative attributes of the fish assemblages among ecoregions. Key conclusions of this work are: (a) the fish-based bioassessment system must be regionalised to reflect biogeographic variation, (b) high faunal heterogeneity among ecoregions (taxonomic, structural), and to a lower degree among basins, constrain the transferability of bioassessment metrics and indices created for explicit regions to other regional frameworks; (c) faunal depauperation in most of the study areas reduce the utility of functional bioassessment metrics and also limits the utilization of rare species and the applicability of the classical form of the “Index of Biotic Integrity” concept. Recommendations to cope with these problems are discussed.

Recent contributions to the distribution of the freshwater ichthyofauna in Greece - N. KOUTSIKOS; S. ZOGARIS; L. VARDAKAS; V. TACHOS; E. KALOGIANNI; R. SANDA; Y. CHATZINIKOLAOU; S. GIAKOUMI; P.S. ECONOMIDIS; A.N. ECONOMOU (Mediterranean Marine Science, 2012)
In this paper we supplement Greece’s recent annotated inventory of freshwater fishes per hydrographic basin with recent distributional data and taxa alteration information, based on field sampling and a literature review up to September 2011. We report on newly documented distributional records of 31 fish species plus one unidentified taxon, within 35 hydrographic river basin units in Greece. These new records include 14 native fish species, seven alien and 12 translocated. Translocated taxa are distinguished from aliens, in order to report species non-indigenous to a basin but native within the same ecoregion. Twelve hydrographic basin units are newly added to the roster of ichthyologically explored river basins following a previous basin-scale inventory method (the total is now 117). This review increases the number of Greece’s freshwater fish taxa to 167, since four new species are added to the list (Carassius langsdorfii, Neogobius fluviatilis, Telestes alfiensis, Millerigobius macrocephalus) and two are deleted (Salmo dentex, Barbus rebeli) due to taxonomic changes. Taxonomic changes will probably continue to alter the national list since phylogenetic research is ongoing on several taxa in many parts of the country